2013
DOI: 10.1016/j.conbuildmat.2013.03.092
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable waste recycling solution for the glass fibre reinforced polymer composite materials industry

Abstract: In this paper the adequacy and the benefit of incorporating glass fibre reinforced polymer (GFRP) waste materials into polyester based mortars, as sand aggregates and filler replacements, are assessed. Different weight contents of mechanically recycled GFRP wastes with two particle size grades are included in the formulation of new materials. In all formulations, a polyester resin matrix was modified with a silane couplin g agent in order to improve binder-aggregates interfaces. The added value of the recyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 36 publications
(43 reference statements)
1
12
0
Order By: Relevance
“…The previous and impending experimental works carried out by the present research team have already demonstrated that GFRP recyclates can be successfully incorporated into PC materials as reinforcement and partial replacement of aggregate components, leading to both flexural and compressive strength increase of modified concrete materials [25,26,[44][45][46][47]. The main outcomes of these studies show that the upcycling of GFRP waste is possible resulting in added value PC products.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…The previous and impending experimental works carried out by the present research team have already demonstrated that GFRP recyclates can be successfully incorporated into PC materials as reinforcement and partial replacement of aggregate components, leading to both flexural and compressive strength increase of modified concrete materials [25,26,[44][45][46][47]. The main outcomes of these studies show that the upcycling of GFRP waste is possible resulting in added value PC products.…”
supporting
confidence: 52%
“…Recently, some experiments were also carried out undertaking the incorporation of GFRP recyclates into polymer concretes (PC) and polymer mortars (PM) [25,26,[44][45][46][47]. The effect of different replacement ratios of sand aggregates by both fine and coarse GFRP waste fractions on final mechanical properties of polyester based PM was assessed, as well as the effect of the incorporation of silane coupling agents.…”
Section: End-use Applications For Gfrp Recyclatesmentioning
confidence: 99%
“…The values are arranged in size from largest to smallest. The most frequently occurring closed pores detected have a volume of around 0.01-0.02 mm 3 . Similar pore volume distributions were detected across all samples.…”
Section: Statistical Analysis Of the Pore Characteristicsmentioning
confidence: 98%
“…possible recycling solutions regarding waste management of composite based products. At present, the main conventional recycling techniques for glass-fiber-reinforced polymer (GFRP) waste materials include incineration, thermal or chemical recycling, and mechanical recycling [1][2][3]. Mechanical recycling through grinding and milling processes is one of the most used techniques; additionally, due to the size reduction of the fibrous products, the recycling process itself does not contribute to atmospheric pollution and much simpler equipment is required as compared to other methods.…”
mentioning
confidence: 99%
“…Several promising applications for fiber reinforced polymer wastes were investigated over the last years (a complete review can be found in Meira Castro et al. []), for example, filler or reinforcement material for artificial wood.…”
Section: Methodsmentioning
confidence: 99%